Could bacteriophages be used as a novel pest management tool to control gut endosymbionts in Western Flower Thrips? - Krueger, Stephanie; Kroj, Andrea; Lehnherr, Tatiana; Lehnherr, Hansjörg; Stuiver, Maarten (Frontiers in Agronomy, 2024)
Several species of Thysanoptera are considered agricultural pests, especially Frankliniella occidentalis (Western Flower Thrips, WFT). The damage WTF causes to plants can either be direct by feeding and oviposition activity, or indirect by WTF serving as vectors for several plant viruses, bacteria, and fungi. Properties of WTF like polyphagy, cryptic lifestyle, fast reproduction and the ability to quickly develop insecticide resistance make them difficult to control. Alternative pest management tactics are thus in high demand. Potential targets are the facultative or obligate endosymbionts that affect the life history parameters of WTF. The known endosymbionts of WFT: BFo1/BFo2 (B = bacteria, Fo = Frankliniella occidentalis, number indicate different types) positively influence their fertility and development in WFT. Eradication Elimination of these endosymbionts could result in a decreased individual reproduction level and decreased population growth. Bacteriophages specific against BFo1/BFo2 were isolated and characterized and were applied in a no-choice feeding assay to female WFT. Antibiotic and sugar solutions served as controls. Phage-treated thrips showed no significant difference in survival, fecundity, oviposition rate or developmental time of the progeny compared to the control, whereas antibiotic treatment caused a decline in survival, fecundity, and oviposition rate, but not in the developmental time of offspring. The results showed a rapid decline of the bacteriophage concentration in the feed solution, which might be caused by the WTF salivary gland products might cause. The complex relationship between thrips, endosymbionts and bacteriophages, needs further attention before bacteriophages could be used as potential management tools.